DEVELOPMENT STRATEGY OF SPORT TOURISM DESTINATION FROM THE PERSPECTIVE OF TALC AND 4A: A CASE STUDY OF DESERT POINT AREA - Asshiddieqy, Hasby; Wardani, Peni Arianita (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Desert Point is one of the world-class surfing destinations located in West Lombok Regency. It holds great potential as a sport tourism destination. However, this potential has not been matched by adequate infrastructure, regulatory frameworks, or formal stakeholder involvement This study aims to formulate development strategies for Desert Point as a sport tourism destination using the Tourism Area Life Cycle (TALC) model, the 4A framework (Attraction, Accessibility, Amenities, Ancillary), and SWOT analysis. A descriptive qualitative method was applied, with data collected through field observations, in-depth interviews, and documentation. The findings indicate that Desert Point is currently in transition from the exploration phase to early involvement. Its attractions, especially the surfing waves and natural scenery, are already strong, but accessibility and supporting facilities remain limited. Based on the SWOT analysis, several short- and medium-term strategies were proposed, including improving access, enhancing digital promotion, providing community training, and initiating land legalization. This research provides practical insights for sport tourism development in remote areas and contributes theoretically by demonstrating the application of TALC as a sustainable destination planning tool.